Gaya Komunikasi Publik Joko Widodo dalam Pemilihan Presiden dan Wakil Presiden - Sukmana, Oman; Komalawati, Euis; Yuliasari, Ika (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The background of this study is situation The 2024 General Election began several years previously with the previous period coalition party bearer candidate president and vice presidential candidate, period after coalition party bearer candidate president and vice presidential candidate formed until approaching announcement candidate presidential and vice presidential candidates by party bearer. In the context that, Joko Widodo Still took office as President and communicated to the public with a diverse style of communication; the study aims to explain and analyze the Communication Style of Joko Widodo's Politics in the Election of President and Vice President in the 2024 General Election. Approach qualitative with paradigm constructivist used through method analysis Roland Barthes' Semiotics. The unit of analysis used is a Kompas TV YouTube video. The result shows Communication Style Joko Widodo's Politics in the Election President and Vice President in the 2024 General Election shows dynamics from before _ nomination President and Vice President, the future is approaching nomination President and Vice President to Commission General Election until the campaign period. In the early days of the General Election, Jokowi showed a Communication Style Controlling Style; in the future, Jokowi's public communication style Structuring Style during the campaign period in a way open, Jokowi pointed out style public communication Dynamic Style.